Proximate analysis of Basak (Justicia adhatoda) leaves powder - Kartick Boxi; Surya Kanta Chanda; Soumyadev Manna; Ranajit Kumar Khalua (The Bioscan, 2024)
The proximate analysis of Justicia adhatoda, commonly known as Basak, is crucial in understanding its nutritional and medicinal properties. This plant, widely recognized for its role in traditional medicine and culinary applications, contains various bioactive compounds that contribute to its health benefits. The proximate composition of Basak leaves includes moisture, ash, protein, crude fibre, fat, carbohydrates, and minerals. This paper reviews the proximate analysis of Basak leaves and their nutritional significance, with a particular focus on their potential as a functional food and medicinal herb.